Neuroimaging of the developing brain: Taking “developing” seriously - Karmiloff‐Smith, Annette (Hum Brain Mapp, 2010)
With a few notable exceptions, many studies, be they behavioral, neuroimaging, or genetic, are snapshots that compare one child group to one adult group, which capture only two points in time and tell the scientist nothing about the mechanisms underlying neural trajectories over developmental time. Thus, a distinction needs to be drawn between child neuroimaging and developmental neuroimaging, the latter approach being relevant not just to children, but to adults and the ageing brain. Hum Brain Mapp, 2010. © 2010 Wiley‐Liss, Inc.